Striatal increase of dopamine receptor 2 density in idiopathic and syndromic mouse models of autism spectrum disorder - Chhabra, Stuti; Nardi, Leonardo; Leukel, Petra; Sommer, Clemens J.; Schmeisser, Michael J. (Frontiers in Psychiatry, 2023)
ABSTRACT Autism spectrum disorder (ASD) comprises a wide range of neurodevelopmental phenotypes united by impaired social interaction and repetitive behavior. Environmental and genetic factors are associated with the pathogenesis of ASD, while other cases are classified as idiopathic. The dopaminergic system has a profound impact in the modulation of motor and reward-motivated behaviors, and defects in dopaminergic circuits are implicated in ASD. In our study, we compare three well-established mouse models of ASD, one idiopathic, the BTBR strain, and two syndromic, Fmr1 and Shank3 mutants. In these models, and in humans with ASD, alterations in dopaminergic metabolism and neurotransmission were highlighted . Still, accurate knowledge about the distribution of dopamine receptor densities in the basal ganglia is lacking. Using receptor autoradiography, we describe the neuroanatomical distribution of D1 and D2 receptors in dorsal and ventral striatum at late infancy and adulthood in the above-mentioned models. We show that D1 receptor binding density is different among the models irrespective of the region. A significant convergence in increased D2 receptor binding density in the ventral striatum at adulthood becomes apparent in BTBR and Shank3 lines, and a similar trend was observed in the Fmr1 line. Altogether, our results confirm the involvement of the dopaminergic system, showing defined alterations in dopamine receptor binding density in three well-established ASD lines, which may provide a plausible explanation to some of the prevalent traits of ASD. Moreover, our study provides a neuroanatomical framework to explain the utilization of D2-acting drugs such as Risperidone and Aripiprazole in ASD.